Lattices of classes of groupoids with one-sided quasigroup conditions - Galuszka, J. (Algebra and Discrete Mathematics, 2010)
It is shown that two classes of groupoids satisfying certain one-sided quasigroup conditions, namely the classes of one-sided torsion groupoids and of one-sided finite exponent groupoids, are complete lattices, both isomorphic to the lattice of Steinitz numbers with the divisibility relation.